Impact of Caring Child with Diabetes Mellitus Type1 upon Mothers at Specialized Center for Endocrinology and Diabetes in Baghdad City (Medico Legal Update, 2020)
The purposes of the study to assess the impact of caring children with Diabetes Mellitus Type 1 upon mothers. A descriptive study was conducted at Specialized Center for Endocrinology and Diabetes in Baghdad City. To achieve the objectives of the study, a (Convenience) samples of (50) mothers who have children with Diabetes Mellitus Type 1. Data were collected by an application of direct interview as a means of data collection. The results indicated that mothers of diabetic children are experiencing a moderate level of burden regarding care of their children (86.5%), in which they are experiencing a moderate psychological and social burden (61.5% and 51.9%), while they show moderate to high financial burden of care for their children (40%). The study concluded that child with Diabetes Mellitus Type I are experiencing a moderate impact on their mothers .